Clients and cases: ambiguity and the division of labour in professional service firms. Issue 4 (14th July 2017) - Alvehus, Johan
Abstract : Purpose: By drawing on a detailed case study of the work of tax consultants, the purpose of this paper is to develop a more detailed understanding of the role of ambiguity in professional work, and its relationship to the division of labour in professional service firms (PSFs). Design/methodology/approach: The paper is based on a three-year, longitudinal interpretive case study comprising 42 interviews, supplemented by observations and document data. Findings: The research determines that processes of "obfuscation" and "privatisation" separate client work from case work. This maintains a division of labour between junior and senior professionals, which in turn facilitates financial leverage. The findings indicate that a more nuanced view on the role and origins of ambiguity is needed; particularly the role ambiguity plays in the division of labour. While inherent in professional work, ambiguity is also an effect of the way work processes are organised in order to obtain leverage. Research limitations/implications: The research is based on a case study. Therefore, the paper explores its topic in empirical detail, but at the same time calls for exploring the topic in different contexts. The paper encourages further research on the role ambiguity plays being constituted by structural arrangements, and on the way the core of professionalism is inverted by the division of labour. The paper highlights the value of detailed empirical approaches for understanding professional work. Practical implications: The paper draws attention to the way ambiguity becomes a part in sustaining a division of labour among professional workers, and to the importance of this in maintaining financial leverage as well as in creating a precarious work situation for junior professionals. Social implications: The paper raises concerns about the way professional work is legitimated in society as opposed to how it is constructed in PSFs. Originality/value: The paper challenges prevalent notions of professional work as ambiguous, offering instead a way of engaging with professional work processes in detail, theoretically and methodologically. Traditional assumptions about the division of labour and the "core" of professional work are problematized, and traditional assumptions about ambiguity as a cause of specific structural arrangements are questioned.